Estudo dos efeitos antinociceptivos e antiinflamatórios de (O-Metil)-N-Benzoil Tiramina (Riparina I) de Aniba Riparia (Nees) Mez (Lauraceae) em camundongos - Araújo, Fernando Luiz Oliveira de (2007)
Riparin I, an alkamide isolated from unripe fruit of Aniba riparia, was evaluated in animal classical models for screening of drugs with antinociceptive, antiinflammatory and antiulcerogenic effects. These models are acetic acid-induced writhing test, formalin test, hot plate test, carrageenan-induced paw oedema, dextran-induced paw oedema, glutamate-induced nociception and paw oedema, indomethacin- and ethanol-induced gastric ulcer. Some behavioral models were used to evaluate if a central activity of drug were involved in antiinflammatory and antinociceptive properties of riparin I. These models are open field, rota rod and pentobarbital-induced sleeping time. Riparin I was administered with doses of 25 and 50 mg/kg, orally and intraperitoneally. The results show that this alkamide did not have effects neither on open field test nor on the rota rod test, discarding the possibility of sedation or motor incordination have influence in antiinflammatory/antinociceptive effects of riparin I. The sedative/hypnotic evaluation in pentobarbital-induced sleeping time shows an increase in sleeping time, probably due pharmacokynetics or sleeping regulation mechanisms, because the sedative effect was not corroborated in the open field test. The open field test is considered more specific than pentobarbital-induced sleeping time. In acetic acid-induced writhing test, riparin I decrease the number of writhies, suggesting an antinociceptive effect. This test is a non-specific test, because antiinflammatory, antidepressant and opioid drugs can decrease the number of writhies. In formalin test, riparin I decrease paw´s licking time in both phases of test, suggesting antinociceptive and antiinflammatory effects. The antinociceptive effect of riparin I seems to be due their antiinflamatory properties, since naloxone could not abolish the antinociceptive effect of riparin I, but, L-arginine could. In the carrageenan-induced paw oedema test, riparin I decrease this parameter, suggesting that riparin I acts inhibiting the syntesis of bradykinin, serotonin, hystamin and prostaglandins, mediators involved in this test. This result probably indicates why riparin I decrease the paw´s licking time in first phase of formalin test, since bradykinin is a common mediator involved in first phase of formalin test and carrageenan-induced paw oedema test. In the dextran-induced paw oedema test, riparin I decrease this parameter, suggesting that riparin I acts inhibiting the syntesis of serotonin and hystamin, mediators involved in this test. Riparin I decreased the ulcerated area induced by indomethacin and ethanol, outstanding your properties like antiinflammatory drug, but not like an ulcerogenic drug. Riparin I could decrease the nociception and the paw oedema, both induced by glutamate, suggesting that riparin I can inhibit the glutamatergic receptors involved in inflammatory processes. In conclusion, riparin I seems act by inhibition of inflammatory mediators like hystamin, serotonin, bradykinin, prostaglandins, glutamate and nitric oxide and seems do not act by opioid system.